2013
DOI: 10.4049/jimmunol.1202645
|View full text |Cite
|
Sign up to set email alerts
|

Ofatumumab Is More Efficient than Rituximab in Lysing B Chronic Lymphocytic Leukemia Cells in Whole Blood and in Combination with Chemotherapy

Abstract: Ofatumumab (OFA) is a human anti-CD20 Ab approved for treatment of fludarabine-refractory B chronic lymphocytic leukemia (B-CLL). The efficacy of different immunotherapeutic strategies is best investigated in conditions that are as physiologic as possible. We have therefore compared the activity OFA and rituximab (RTX), alone or in combination with chemotherapeutic agents in unmanipulated whole blood assays, using flow cytometry. OFA (10–100 μg/ml) lysed B-CLL targets in whole blood more efficiently and with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(82 citation statements)
references
References 40 publications
6
74
0
2
Order By: Relevance
“…The mAb ofatumumab is capable of lysing a range of rituximab-resistant targets, in particular CD20 low expressing cells. 49,50 In B-CLL cells, expressing both CD52 and low levels of CD20, alemtuzumab-mediated CDC can further be enhanced by the addition of ofatumumab. 51 The clinical response rate to rituximab has been shown to rely on the CD20 expression level, which is consistent with data on in vitro CDC induction.…”
Section: The Role Of Complement In Ab Immunotherapymentioning
confidence: 99%
“…The mAb ofatumumab is capable of lysing a range of rituximab-resistant targets, in particular CD20 low expressing cells. 49,50 In B-CLL cells, expressing both CD52 and low levels of CD20, alemtuzumab-mediated CDC can further be enhanced by the addition of ofatumumab. 51 The clinical response rate to rituximab has been shown to rely on the CD20 expression level, which is consistent with data on in vitro CDC induction.…”
Section: The Role Of Complement In Ab Immunotherapymentioning
confidence: 99%
“…1A). [6][7][8][9][10][11][12][13] These mechanisms depend on the Fc portion of the antibody binding to FcγRs on immune cells. In addition, RTX and other anti-CD20 antibodies can activate signaling pathways after binding of the Fab portion to CD20 on B cells and induce homotypic adhesion (aggregation of target cells) and/or cell death to a variable extent (Fig.…”
Section: Rtx Pdmentioning
confidence: 99%
“…23 It exhibits more potent complement-dependent cytotoxicity (CDC) and antibody-dependent cellular cytotoxicity (ADCC) compared with rituximab in B-cell lines including CLL cells. [24][25][26] Ofatumumab is approved in the United States for treatment of CLL refractory to fludarabine and alemtuzumab 27 and in combination with chlorambucil for previously untreated CLL where fludarabine-based treatment is inappropriate. 28,29 Studies with single-agent ibrutinib showed early lymphocytosis in patients with CLL, [30][31][32] which is considered a pharmacodynamic effect of ibrutinib resulting in mobilization of lymphocytes into the peripheral blood from tissue compartments.…”
Section: Introductionmentioning
confidence: 99%